Case study on Good Samaritan Nursing Home effects of selected interior design elements on proximics among the elderly patients in living areas - Cacayan, Hannah Noelle J.; Brasileño, Lynne I. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
The study explored the effects of selected interior design elements such as space size and layout, quantity and arrangement of furniture, acoustics, and lighting, toward the social communication and interpersonal distance among the elderly patients in the living areas from Good Samaritan Nursing Home. The interior design of the common space must cater to the elderly persons' dynamic and changing preferences for privacy and social interaction. The study aimed to describe the current condition of the living areas, to explain how the selected interior design elements in the living areas affected the quality and regulation of social interaction among the elderly, and to analyze if these elements addressed each person's need for desired level of privacy and interaction. A qualitative approach in a form of case study and quota sampling were used to select the site and the respondents for in-depth interviews. The respondents of this study included five elderly patients. The administrator of the nursing home was also interviewed. The instrumentation included interview guides and camera for photo documentation. The analysis consisted of each of the elderly patient's perception and social behavior towards each interior design element. Hall's Theory of Proxemics and the concepts of social engagement and of privacy in the context of the Philippine society were used to analyze how the selected interior design elements affected the social behavior among the elderly patients. Based on the findings, one of the major concerns of the respondents were the limited size and layout of the space. It was because they need more movement and space around the space to get closer to or away from someone due to physical limitations brought about by aging. The areas also lack of seating furniture to accommodate the elderly; based on the elderly respondents' perceptions, the socio-petal arrangement of furniture was preferred to encourage social interaction. Noises caused by other users and appliances of the living area were also viewed as an intrusion of personal space and disturbance of social interaction among the elderly. The brightness and dimness of the lighting also affected the communication among the elderly, since the elderly respondents were already experiencing problems with vision. Most of the respondents perceived the current general lighting condition within the living areas as insufficient to support social interaction. In this study, interior design elements are perceived as key considerations in fostering social interaction and the need for privacy among the elderly.
submitted June 2017
Thesis (B.S. Interior Design)--University of the Philippines Diliman.
Keywords: Nursing homes -- Philippines -- Interior decoration